Critical Thinking Abilities Students Solving Social Arithmetic Numeracy Problems Based On Initial Mathematics Proficiency - Pramesti, Hardita Arum; Sari, Christina Kartika (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2024)
This study aims to present the results of the analysis of critical thinking skills of students with low, medium, and high initial abilities in solving social arithmetic numeracy problems and to determine the critical thinking skills of students in each critical thinking indikator. Critical thinking ability is an important skill that students must have to evaluate information, make rational decisions, and solve problems effectively. Students trained in critical thinking have the ability to face problems, examine them, and find appropriate solutions. This research is qualitative research with descriptive qualitative method. The research subjects were seventh grade junior high school students in Surakarta. Data were colleccted through written tests, student interviews, and observations. The results and conclusion of this study indicate that students’mathematical critical thonking skills on social arithmetics material in terms of initial ability are still relatively low, from the results of the analysis based on the four critical thinking indicators that are the reference in this study students tend not to be able to fulfill the four critical thinking indicators.